Obstetric outcomes in late pregnancy in the southern Tocantins region (Research, Society and Development, 2023)
Late pregnancy is the term used to characterize women who become pregnant after the age of 35, whether it is a planned pregnancy or not. It is a reality that grows all over the world, a trend of women of this time, caused by several factors, among them, the desire for professional fulfillment. This research aims to describe the obstetric outcomes of late pregnancies in the Southern Region of Tocantins, from 2019 to 2021. It is a descriptive, exploratory, retrospective, documentary study with a quantitative approach, with data obtained through of the Information System on Live Births (SINASC). The study sample consisted of a total of 455 records of pregnant women over 35 years of age. That women have increasingly postponed pregnancy, not necessarily with marital relations but with management, aiming at finishing their studies and entering the job market. Every day the number of cesarean sections increases due to the benefits of natural childbirth for this faixeria.